A lawman's Christmas : a McKettricks of Texas novel - Miller, Linda Lael. (Don Mills, Ont. : HQN, 2011)
The sudden death of the town marshal leaves Blue River, Texas, without a lawman, and Dara Rose Nolan without a husband or income, until Clay McKettrick comes to town. When they say "I do" to a marriage of convenience, the temporary lawman's wish is to make Dara Rose his permanent wife.
Keywords: Christmas stories; Texas -- Fiction; Love stories; Western stories